EFFECT OF BUSINESS STRATEGY ON COMPETITIVE ADVANTAGE IN PRIVATE UNIVERSITIES IN SOMALIA - kising‟u ,PhD, Dr. Titus M.; RAGE, MAHAD ADAN (IJRDO - Journal of Business Management, 2018)
The general objective of this study is to investigate the business strategy of competitive advantage among private Universities in Somalia. Specifically, this study was investigate the effects of cost leadership, growth strategies, differentiation strategies and market focus strategies on competitive advantage among private universities in Somalia. Competitive success is enhanced by moving early in each product or process generation, provided that the movement is along a path that reflects evolving technology and buyer need, and that early movers subsequently upgrade their positions rather than rest upon them. In this view, firms have considerable discretion in relaxing external and internal constraints. Identified academic and programmed issues, cost of education, location and recreation facilities and peer and family influences as four of the most important factors that influence students’ choice of tertiary institution and business strategy play the effectiveness and efficiency in private Universities. The target population of this study was 100 and a proportionate sample size of approximate 80 respondents. The population was select using purposive sampling or judgmental sampling technique. The sampling procedure of this study was used non-probability sampling procedure particularly purposive sampling or judgmental sampling.. The data collected was analyzed using the software called Statistical Package for the Social Sciences (SPSS) version 20 and results shown in terms of frequency distribution and percentages. A regression model was applied to determine the relationship between cost leadership, growth strategies, differentiation strategies and market focus strategies as independent variable on competitive advantage as the dependent variable. The most researchers have focused on competitive strategies adopted by universities in Somalia (Abdinor 2015). The researchers explored the competitive strategies adopted by Somalia Universities and the challenges experienced in implementing these strategies but they did not research how to gain competitive advantage or business strategy of competitive advantage among private universities. Results confirm the varying importance of the business strategy of competitive advantage among private universities in Somalia. In general, the results reveal that Cost leadership strategy, growth strategy, differentiation strategy has significance effect on competitive advantage and market focus strategy has insignificance effect on competitive advantage. The study recommends that private Universities should highly invest in market research this would help in development of unique degree programs that are relevant to the current economic trends. Innovation of these distinctive programs will increase in selling institutions image thus helping to capture new markets. The study recommends that private universities should consider sub-standardizing the cost of the programs they offer, this move is very critical based on the finding that the target population choice is usually influenced by cost of the programs in comparison to those of its rivals. The research recommends that private universities should consider outsourcing some activities (but to professionals) which are not closely related to the universities strategic plan, this would allow concentration of efforts on the main strategic goal thus enhancing probability of excellence.